Pemanfaatan Daun Kemuning Sebagai Obat Tradisional Penyakit Asma - Riska Nanda Safitri; Mustika Elmi Dayana; Vinna Cientya Annisa; Dita Aulia; Dewi Jumiarni (University of Bengkulu, 2020)
Kemuning (Murraya paniculata L) is a shrub growing in tropical climates and wildly in bushland or forest. The local people of Serawai ethnicin Bengkulu often use kemuning leaves as a traditional medicine for asthma disease. . This study aims to analyze the potential and benefits of Kemuning (Muraya paniculata L) leaves as a traditional medicine forasthma disease. This research is a descriptive study by using interview method with Snow ball sampling techniques. The results showed that Murraya paniculata leaves have been empirically proven to treat asthma in Serawai tribe community. The leaves are processed by squeezing, filtering, then drinking or smearing it on the chest. The presence of flavonoids in Murraya paniculata leaves thought have the effect of reducing asthma. Murraya paniculata leaves have potential to be developed as an asthma medicine, but further research is needed before using in the pharmaceutical industry.